To simplify the expression −25x^8/5x, we can apply the properties of exponents.
First, let's simplify the numerator. According to the property of exponents, when dividing exponents with the same base, we subtract the exponents. So, x^8 / x = x^(8-1) = x^7.
Now, the expression becomes -25x^7/5x. Next, let's simplify the coefficient -25/5. -25/5 = -5.
Finally, we have -5x^7/ x. According to the property of exponents, when dividing exponents with the same base, we subtract the exponents. So, x^7 / x = x^(7-1) = x^6.
Therefore, the simplified expression is -5x^6.
Expand the properties of exponents to involve monomial bases with integer exponents to simplify the expression −25x^8/ 5x
3 answers
Thats not an option
Apologies for the confusion. Let's simplify the expression correctly.
To simplify the expression −25x^8/5x, we can simplify the coefficients and apply the properties of exponents.
First, simplify the coefficient: -25/5 = -5.
Next, simplify the variables: x^8 / x^1 = x^(8-1) = x^7.
Now, the expression becomes -5x^7.
Therefore, the simplified expression is -5x^7.
To simplify the expression −25x^8/5x, we can simplify the coefficients and apply the properties of exponents.
First, simplify the coefficient: -25/5 = -5.
Next, simplify the variables: x^8 / x^1 = x^(8-1) = x^7.
Now, the expression becomes -5x^7.
Therefore, the simplified expression is -5x^7.